Revolution of Financial Reporting of Chinese Listed Companies 2001-2005: Information Disclosure of Corporate Governance - Zhang, Shu (2006)
Corporate governance is relatively new topic in Chinese annual reporting system, whilst China is making significant progress to make the disclosure close to the international standards. However, there is hardly any study or literature documenting the disclosure practice regarding to corporate governance in China. This study focuses on the annual reports of the companies in the two Chinese stock exchanges aiming at accessing the simplicity and quality of the corporate governance information. Twenty listed companies are primarily selected to form the sample of internet disclosure testing. Nineteen companies' annual reports are found available on the Internet, and the overall voluntary Internet disclosure is polarized: nothing at all or very detailed. The research carried out in corporate governance disclosure found that the changing intention corresponded with the previous studies. The actual corporate governance statement still plays an outside part, despite the Chinese regulators published the code for corporate governance. The conclusion made is that the fundamental improvement of Chinese corporate governance disclosure is to introduce the corporate governance statement. However, due to the limitations of this study, it is suggested that further study should carried on examining the actual corporate governance statement in an enlarged samples size, and it is ideally computer assisted.